Implementasi Program Bina Keluarga Di Jemaat Gpi Papua Imanuel Danaweria Fakfak - Ohoiner, Holly Desemrine; Ngabalin, Ngabalin; Rewasan, Ruben; Camerling, Lindra Yolanda (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2023)
The family development program is a form of formation for church members. This formation starts from the family where parents provide spiritual formation for their children in the form of family worship. Within the scope of GPI Papua's services in general and the GPI Papua Imanuel Werba congregation in particular, family development is not a congregational service program but rather was born from the awareness of the congregation to do so.This research aims to describe the congregation members' understanding of the family development program at the GPI Papua Imanuel Danaweria congregation; Describe the Implementation of Family Development in the GPI Papua Congregation Imanuel Danaweria; Mention factors inhibiting the progress of family development in the family;Describes the impact of the family development program in the GPI Papua Congregation Imanuel Danaweria.The research results show that family development is development that is centered on family development. Providing knowledge of the Christian faith for children, forming and developing the attitudes and character of family members to live according to their faith and the family to live happily and in harmony. Family formation is carried out in the form of family worship on Saturdays in every Christian family in the congregation or known as family worship. Where the father is the leader and main person responsible for the service because it includes not only the ministry of the word but also advice and upbringing given by the head of the family to both wife and children or parents to children. Family formation is carried out in the form of family worship on Saturdays in every Christian family in the congregation or is known as the key family service. Where the father is the leader and main person responsible for the service because it includes not only the ministry of the word but also advice and upbringing given by the head of the family to both wife and children or parents to children. This family development does not run completely because there are factors that hinder the progress of the Binakel worship, namely the work factor of each family member, social factors so that some children are not actively involved in worship and the factor of laziness from within. family members to perform the prayer. The impact of family development shapes the character of family members so they are better able to implement their faith in God in the realities of everyday lifeAbstrakProgram bina keluarga merupakan salah satu bentuk pembinaan warga gereja. Pembinaan tersebut dimulai dari keluarga di mana orang tua melakukan pembinaan spiritual bagi anak-anak dalam bentuk ibadah keluarga. Dalam lingkup pelayanan GPI Papua secara umum dan jemaat GPI Papua Imanuel Danaweria secara khusus bina keluarga tersebut tidak menjadi program pelayanan jemaat melainkan lahir dari kesadaran umat untuk melakukannya. Penelitian ini bertujuan untuk Mendeskripsikan pemahaman warga jemaat tentang program Bina keluarga di Jemaat GPI Papua Imanuel Danaweria; Mendeskripsikan Implementasi Bina keluarga di Jemaat GPI Papua Imanuel Danaweria; Menyebutkan faktor penghambat jalannya Bina keluarga dalam keluarga; Menguraikan dampak program Bina keluarga di Jemaat GPI Papua Imanuel Danaweria. Hasil penelitian menunjukkan bahwa Bina keluarga merupakan pembinaan yang berpusat pada pembinaan keluarga. Memberi pengetahuan iman Kristen bagi anak, membentuk dan membina sikap dan karakter anggota keluarga untuk hidup sesuai dengan imannya dan keluarga hidup Bahagia dan rukun. Bina keluarga yang dilakukan dalam bentuk ibadah keluarga pada hari sabtu di setiap keluarga Kristen di jemaat atau dikenal ibadah kunci usbuh keluarga. Di mana bapak menjadi pemimpin dan penanggung jawab utama dalam ibadah tersebut sebab di dalamnya tidak hanya ada pelayanan firman tetapi juga nasihat dan didikan yang diberikan oleh kepala keluarga baik bagi istri dan anak-anak atau orang tua kepada anak. Bina keluarga ini tidak berjalan sepenuhnya dikarenakan ada faktor yang menghambat jalannya ibadah Binakel yaitu faktor pekerjaan dari masing-masing anggota keluarga itu sendiri, faktor pergaulan sehingga anak ada yang tidak terlibat secara aktif dalam ibadah serta faktor kemalasan dari dalam diri anggota keluarga untuk melakukan ibadah tersebut. Dampak dari bina keluarga tersebut membentuk karakter anggota keluarga menjadi lebih dapat mengimplementasikan iman percayakan kepada Tuhan dalam realitas hidup setiap hari.